2013
DOI: 10.1055/s-0033-1340465
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Chemoenzymatic Synthesis of (RS)-, (R)-, and (S)-Bunitrolol

Abstract: A new chemical and the first chemoenzymatic synthesis of β-adrenergic receptor blocking agent bunitrolol is reported in racemic (RS) and enantioenriched forms (R and S). The intermediates (R)-and (S)-1-chloro-3-(2-cyanophenoxy)propan-2-ol intermediates were synthesized from the corresponding racemic alcohol through enzymatic kinetic resolution. The commercial available lipases PS-C and CCL exhibited complementary enantioselectivity during transesterification of the racemic alcohol with vinyl acetate affording … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
(13 reference statements)
0
5
0
Order By: Relevance
“…It was found that, with the increase in the enzyme amount, the conversion rate increased and reached a peak with a conversion efficiency of uridinetouridine monoester observed to be 96.06% at 40 mg/mL and then gradually started forming diester with 80,120 mg/mL lipase ( Figure S4 ). 12 a–d…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was found that, with the increase in the enzyme amount, the conversion rate increased and reached a peak with a conversion efficiency of uridinetouridine monoester observed to be 96.06% at 40 mg/mL and then gradually started forming diester with 80,120 mg/mL lipase ( Figure S4 ). 12 a–d…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, our main focus has been on developing an efficient pathway to obtain Molnupiravir (route D) by employing a two-step process that involves the production of a regioselective monoacylated intermediate. Lipase, a highly versatile biocatalyst, has been extensively used for the kinetic resolution of racemic alcohols for the synthesis of enantiopure drugs and drug intermediates . Due to its high chemo-, regio-, and stereoselectivity, which encouraged us toward the synthesis of Molnupiravir, lipase was selected for the biocatalytic regioselective acylation of uridine in this study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lipase was one of the first enzymes to be utilized as a biocatalyst in the 1980s, and it has since been developed for a variety of chemo enzymatic reactions, [30][31][32][33][34][35][36] owing to its stability in terms of pH, organic solvent, temperature, and other physical parameters. [37][38][39] 3.1 | Optimization of reaction condition with lipases, acyl donor, course of time interval, temperature, and so forth…”
Section: Resultsmentioning
confidence: 99%
“…Lipase was one of the first enzymes to be utilized as a biocatalyst in the 1980s, and it has since been developed for a variety of chemo enzymatic reactions, 30‐36 owing to its stability in terms of pH, organic solvent, temperature, and other physical parameters 37‐39 …”
Section: Resultsmentioning
confidence: 99%